An investigation on the validity of power-direction method for harmonic source determination. - Wilsun Xu (IEEE Transactions on power delivery)
The power-direction method has been used widely to identify the locations of harmonic sources in a power system. A number of utility-customer disputes over who is responsible for harmonic distortions have been settled with the help of the method. A closer examination of the method, however, reveals that it is unable to fulfil the task of harmonic source detection. Case studies can easily show that the method yields incorrect results. In this paper, problems associated with the method are investigated using case studies and mathematical analysis. The results show that the power direction method is theoretically incorrect and should not be used to determine harmonic source locations. The main cause of the problem is that the direction of active power flow is a function of the phase-angle difference between the two sources. The direction of reactive power flow, on the other hand, has a better correlation with the source magnitudes.